DNA methylation associated with polycomb repression in retinoic acid receptor β silencing. Issue 4 (8th January 2013) - Moison, Céline; Senamaud‐Beaufort, Catherine; Fourrière, Lou; Champion, Christine; Ceccaldi, Alexandre; Lacomme, Stéphanie; Daunay, Antoine; Tost, Jörg; Arimondo, Paola B.; Guieysse‐Peugeot, Anne‐Laure
Abstract : Retinoic acid receptor β 2 ( RAR β 2 ) is a tumor suppressor gene whose loss of expression is recurrent in prostate cancers. Here we studied the epigenetic mechanisms leading to its stable silencing. First, we characterized all RAR β isoforms in 6 human tumor cell lines (prostate DU145, LNCaP, PC3, lung A549, breast Hs578T, and colon HCT116) by RT‐PCR and Western blot. We excluded loss of heterozygosity (2D‐FISH) and loss of RARa expression, an upstream regulator, as origin of RAR β 2 silencing. All data concluded to an epigenetic silencing. In agreement, a DNA methylation inhibitor restored its expression. Second RAR β 2 loss of expression was found associated with different epigenetic profiles in LNCaP and DU145 cells. According to bisulfite sequencing and ChIP analysis, we observed heavy methylation (97%) of the RAR β 2 promoter with repressive histone mark H3K9me3 in LNCaP. While DNA methylation and polycomb repression are described to be mutually exclusive at CpG‐rich promoters, we observed that in DU145, moderate DNA methylation (36%) and H3K9me3 mark were present concomitantly with H3K27me3, a signature of polycomb repression. In summary, we provide new insights on how the RAR β 2 promoter is silenced, reveal the existence of two distinct repressive chromatin profiles at the same locus, and support a polycomb‐mediated epigenetic repression process in prostate cancer.—Moison, C., Senamaud‐Beaufort, C., Fourrière, L., Champion, C., Ceccaldi, A., Lacomme, S., Daunay, A., Tost, J. Arimondo, P. B., Guieysse‐Peugeot, A.‐L. DNA methylation associated with polycomb repression in retinoic acid receptor β silencing. FASEB J. 27, 1468–1478 (2013). www.fasebj.org